Ecología y distribución del bejuco negro (Smilax tomentosa Kunth) con miras al co-diseño de estrategias de mitigación de movimientos en masa en el complejo volcánico Doña Juana-Cascabel (2021)
The black vine (Smilax tomentosa Kunth) is currently the focus of study of an interdisciplinary project carried out by the group of Historical Ecology and Social Memory (EHMS) of the University of the Andes, which seeks to create strategies to mitigate land displacement in Mount Montoso (Nariño). However, little is known about this vine, so this study seeks to compile all the existing information on the ecological, histological and natural history of this vine, in addition to reviewing the GBIF herbarium sheet files and modeling the species niche to understand more about the abiotic factors that affect its distribution. Mean, max and min temperature throughout the year was found as an important climatic determinant; and the cation exchange capacity as the most relevant soil factor for its growth, which is closely related to the high content of clay and organic matter typical of volcanic soils.